Practicing philosophy as experiencing life : essays on American pragmatism - Skowroński, Krzysztof Piotr. (Value Inquiry Book Series, 2015)
Practicing Philosophy as Experiencing Life: Essays on American Pragmatism is a collection of texts written by top international experts on American philosophy. They consider various strands of American pragmatism from the viewpoint of practical philosophy, and provide the historical background and an outline of the international encounter with other philosophical traditions. Many key figures of American thought and pragmatist philosophy are discussed. The volume combines a panorama of approaches and gives a wide scope of problems: ethical, religious, social, political, cultural, ontological, cognitive, anthropological, and others, so as to show that pragmatism can be seen as a philosophy of life and as such it focuses on the life problems of contemporary humans in particular and of humanity in general. Contributors are: Jacquelyn Ann K. Kegley, John Lachs, Sami Pihlström , Krzysztof Piotr Skowroński, Kenneth W. Stikkers, and Emil Višňovský